2003
DOI: 10.1159/000075129
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol, 1-Palmitoyl-2-Linoleoyl-3-Acetyl-<i>rac </i> -Glycerol Isolated from Bovine Udder and its Synthetic Enantiomer can Potentiate the Mitogenic Activity for Mouse Peritoneal Macrophages

Abstract: A factor stimulating a mitogenic activity of peritoneal macrophages is purified from bovine udder. It is identified as a triglyceride, 1-palmitoyl-2-linoleoyl-3-acetyl-rac -glycerol (rac -MADG). In this study, its enantiomers, R-(+)-and S-(-)-1-palmitoyl-2-linoleoyl-3-acetylglycerol (R-(+)-MADG, S-(-)-MADG) are synthesized. Among them, R-(+)-MADG enantiomer turns out to increase a mitogenic activity in mouse peritoneal macrophages. Also, (S)-(-)-MADG shows a low mitogenic activity. Treatment of a macrophage wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…22 Isolated peritoneal macrophages were cultured in RPMI medium 1640 containing 10% FCS overnight at 37°C and 5% CO 2 , and labeled with 35 S-methionine as described previously. 23 Recombinant hLPLwt and hLPL156 were recovered from the media by immunoprecipitation using a monoclonal anti-LPL antibody.…”
Section: Characterization Of Macrophages From Transgenic Micementioning
confidence: 99%
“…22 Isolated peritoneal macrophages were cultured in RPMI medium 1640 containing 10% FCS overnight at 37°C and 5% CO 2 , and labeled with 35 S-methionine as described previously. 23 Recombinant hLPLwt and hLPL156 were recovered from the media by immunoprecipitation using a monoclonal anti-LPL antibody.…”
Section: Characterization Of Macrophages From Transgenic Micementioning
confidence: 99%
“…In traditional oriental medicine, Sika deer antler is considered to have beneficial therapeutic properties for the treatment of a wide variety of medical conditions, including mastitis, uterine fibroids, and mammary hyperplasia [ 19 ]. Sika deer antler contains a number of ingredients, among which it has recently been shown that monoacetyldiaglyceride has pharmacological properties, including hematopoietic and antitumor effects [ 21 , 34 , 35 ]. Although EC-18 was initially approved as a functional food in Korea, the United States FDA approved EC-18 for the treatment of severe chemotherapy-induced neutropenia in patients with advanced breast cancer being treated with intermediate febrile neutropenia risk chemotherapy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%